Identification and mycotoxigenic capacity of fungi associated with pre- and postharvest fruit rots of pomegranates in Greece and Cyprus - Kanetis, Loukas; Testempasis, Stefanos; Goulas, Vlasios; Samuel, Stylianos; Myresiotis, Charalampos K.; Karaoglanidis, George S. (My University, 2015)
Pre- and postharvest fruit rots of fungal origin are an important burden for the pomegranate industry worldwide, affecting the produce both quantitatively and qualitatively. During 2013, local orchards were surveyed and 280 fungal isolates from Greece (GR) and Cyprus (CY) were collected from pomegranates exhibiting preharvest rot symptoms, and additional 153 isolates were collected postharvest from cold-stored fruit in GR. Molecular identification revealed that preharvest pomegranate fruit rots were caused predominately by species of the genera Aspergillus (Aspergillus niger and Aspergillus tubingensis) and Alternaria (Alternaria alternata, Alternaria tenuissima, and Alternaria arborescens). By contrast, postharvest fruit rots were caused mainly by Botrytis spp. and to a lesser extent by isolates of Pilidiella granati and Alternaria spp. Considering that a significant quota of the fungal species found in association with pomegranate fruit rots are known for their mycotoxigenic capacity in other crop systems, their mycotoxin potential was examined. Alternariol (AOH), alternariol monomethyl-ether (AME) and tentoxin (TEN) production was estimated among Alternaria isolates, whereas ochratoxin A (OTA) and fumonisin B2 (FB2) production was assessed within the black aspergilli identified. Overall in both countries, 89% of the Alternaria isolates produced AOH and AME in vitro, while TEN was produced only by 43.9%. In vivo production of AOH and AME was restricted to 54.2% and 31.6% of the GR and CY isolates, respectively, while none of the isolates produced TEN in vivo. Among black aspergilli 21.7% of the GR and 17.8% of the CY isolates produced OTA in vitro, while in vivo OTA was detected in 8.8% of the isolates from both countries. FB2 was present in vitro in 42.0% of the GR and 22.2% of the CY isolates, while in vivo the production was limited to 27.5% and 4.5% of the GR and the CY isolates, respectively. Our data imply that mycotoxigenic Alternaria and Aspergillus species not only constitute a significant subset of the fungal population associated with pomegranate fruit rots responsible for fruit deterioration, but also pose a potential health risk factor for consumers of pomegranate-based products.
Keywords: Alternaria; Alternariol; Ochratoxin A; Alternariol monomethyl-ether; Fumonisin B2; Aspergillus